Effects of Dissolved Oxygen Tension and Ammonium Concentration on Polyhydroxybutyrate Synthesis from Cassava Starch by Bacillus cereus IFO 13690 - M. Margono; R. Rochmadi; Siti Syamsiah; Muhammad Nur Cahyanto (Universitas Gadjah Mada, 2009)
Attempting to get low price of raw material for producing polyhydroxybutyrate is always studied. Tapioca starch is one of the raw material with low price. The objective of this research was to study the effects of initial ammonium concentration and dissolved oxygen tension (doT) on producing PHB by Bacillus cereus IFO 13690 with tapioca starch as the carbon source. This fermentation was carried out in 5 L fementors with a 2 L working volume, temperature of 30 oC, and agitation of 500 rpm. The pH medium was controlled at 5.6 after it came down from the initial pH of 6.8. Meanwhile, the initial doT was 100 % air saturation and also came down to and maintained at doT of experiment, i.e. 1 , 5 , or 10 % air saturation. The best result was obtained when the initial ammonium concentration was 5 g/L and the doT value maintained at 5 % air saturation. By this conditions, the cell growth reached 5,457 g cell dry weight/L containing PHB of 2.42 % cell dry weigh after 29 hours fermentation.